Determinants of the competitiveness of the capital goods industry in Spain and Germany (1993-2008): absolute advantage of cost, wage and productivity - Boundi, Fahd (Papeles de Europa, 2014)
This paper makes a comparative analysis of the capital goods industry in Spain and Germany, in order to explain the determinants of competitiveness in this industry. The main hypothesis is: the German capital goods industry is more competitive as a result of its higher productivity and its lower relative costs. Thus, we will start from the classical and Marxian theory of price formation, and the model of the absolute advantages of Anwar Shaikh. Subsequently, the rates of real unit labor costs are calculated and the absolute advantage’s theory is tested empirically.
Keywords: prices; labor cost; productivity; international trade; absolute advantage